KETERLIBATAN KAUM AWAM KATOLIK DALAM BIDANG POLITIK Studi Kasus di Desa Banjarsari pada Tahun 2012-2013 - Prasetya Handaya Wicaksana (P3TK, Sanata Dharma University, 2014)
Main purpose of politics is common participation for a common good, which allows the people to live well and fully in a society. Although Catholic Church may not confused religion and politics, she cannot ignore socio-political affairs. Thus, she is called to be witness of Christ who preached the Kingdom of God. Christian faith encourages the Church to have a certain attitude towards socio-political conditions in our society. To create a common good is indeed a vocation for all the faithful. This article aims to inquire the presence and role of laity as local leaders, as part of the Church's involvement in the political sphere, based on the observation in Banjarsari Village. Using a qualitative approach, this article aims to see the link between the involvement of the laity in politics with the teachings of the Catholic Church regarding politics. The results show that the values of churchs teaching have been greatly lived in their participation in a society. Faith helps them to build awareness of their social and political responsibility.